2015
DOI: 10.3109/10826084.2015.978189
|View full text |Cite
|
Sign up to set email alerts
|

What Causes Addiction Problems? Environmental, Biological and Constitutional Explanations in Press Portrayals From Four European Welfare Societies

Abstract: Press items (N = 1327) about addiction related problems were collected from politically independent daily newspapers in Finland, Italy, the Netherlands, and Poland from 1991, 1998, and 2011. A synchronized qualitative coding was performed for discerning the descriptions of the genesis to the problems in terms of described causes to and reasons for why they occur. Environmental explanations were by far the most common and they varied most between the materials. The analysis documents how the portrayals include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Researchers have also argued that the formula story in which opiate addiction is an incurable condition tends to become a self-fulfilling prophecy in the treatment system (Järvinen, 2014; Järvinen & Andersen, 2009). Cross-cultural studies have revealed that international differences in circulating stories about substance use problems can be traced back to different welfare cultures in different countries (Beccaria et al, 2015; Hellman et al, 2015; Hellman & Room, 2015). In the Nordic countries, the welfare system is characterized by “social democratic” principles such as universalism and an institutionalized commitment to welfare (Esping-Andersen, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have also argued that the formula story in which opiate addiction is an incurable condition tends to become a self-fulfilling prophecy in the treatment system (Järvinen, 2014; Järvinen & Andersen, 2009). Cross-cultural studies have revealed that international differences in circulating stories about substance use problems can be traced back to different welfare cultures in different countries (Beccaria et al, 2015; Hellman et al, 2015; Hellman & Room, 2015). In the Nordic countries, the welfare system is characterized by “social democratic” principles such as universalism and an institutionalized commitment to welfare (Esping-Andersen, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on media coverage (Beccaria et al, 2015; Hellman & Room, 2015; Törrönen, Simonen, & Tigerstedt, 2015; Winter, 2016), social media (Dwyer & Fraser, 2016), classical literature (Allamani & Mattiacci, 2015), and film (Egerer, 2013; Room, 2015) demonstrate that storytelling and conceptualizations of substance use problems vary over time and place. Cross-cultural variations in media narratives are found to reflect basic beliefs and assumptions that societies hold about people with substance use problems (Beccaria et al, 2015; Hellman, Majamäki, Rolando, Bujalski, & Lemmens, 2015; Hellman & Room, 2015).…”
Section: Formula Stories and Client Identitiesmentioning
confidence: 99%
“…Campbell 2012); and press portrayals (e.g. Hellman et al 2015) to identify the perspectives used to frame addiction problems. For example, biological explanations were not found to be predominant in press portrayals of addiction problems in Finland, Italy, Poland, and the Netherlands (Hellman et al 2015).…”
Section: The Social Context Of News Reportingmentioning
confidence: 99%
“…Hellman et al 2015) to identify the perspectives used to frame addiction problems. For example, biological explanations were not found to be predominant in press portrayals of addiction problems in Finland, Italy, Poland, and the Netherlands (Hellman et al 2015). However, in the present article, reductionism is instead conceptualized as the extent to which the media reports of biomedical alcohol research focus on biological factors only.…”
Section: The Social Context Of News Reportingmentioning
confidence: 99%
See 1 more Smart Citation